Offline image reconstruction for optical tomography - 296151 Chan, Kok San (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering (Control & Instrumentation)) - Universiti Teknologi Malaysia, 2001